Antibiofilm Activities of Bioactive Compounds of Local Edible Flowers in Indonesia: A Review - Anwar Rovik; Laelatul Afifah; Nur Rokhmalia; Vania Uly Andyra; Richad Richad (Universitas Sebelas Maret, 2024)
Antimicrobial resistance is a growing global health problem. Biofilm formation is a notable risk factor for patient mortality. Various efforts are needed to prevent biofilm formation. Plants have been utilized in traditional medicine practices for centuries. In this review, we present an ethnobotanical study of the use of edible flowers in Indonesia and their potential development as antibiofilm agents. Local communities in Indonesia have long used various flowering plants for traditional ceremonial purposes, aesthetics, cooking ingredients, and medicine. Only a few types of flowers are utilized as food ingredients or edible flowers. There are 25 types of edible flowers from 19 families in Indonesia. Not all edible flowers in Indonesia have been studied for their antibiofilm activities. The presence of bioactive compounds, e.g., alkaloids, saponins, steroids, terpenoids, flavonoids, and phenolics in edible flowers, suggests that they may have the potential to inhibit biofilm formation. Local communities also use edible flowers in traditional medicine practices, including Hibiscus sabdariffa, Jasminum sambac, Caesalpinia pulcherrima, Punica granatum, Blumea balsamifera, and Lantana camara. The bioactive compounds showed antimicrobial activity against Gram-positive and Gram-negative bacteria, including Acinetobacter baumannii, Vibrio cholerae, Staphylococcus aureus, Bacillus cereus, Listeria spp., Streptococcus spp., Enterococcus faecalis, Salmonella typhi, Shigella dysenteriae, Escherichia coli, Klebsiella spp., Proteus spp., Porphyromonas gingivalis, and Treponema denticola. We also highlight the need for further research to explore more edible flowers and their specific effects of the compounds on biofilm formation.